Biodiversity of Angola Science & Conservation: A Modern Synthesis - Huntley, Brian J.; Russo, Vladimir; Lages, Fernanda; Ferrand, Nuno (Springer International Publishing : Imprint: Springer, 2019)
This open access multi-authored book presents a 'state of the science' synthesis of knowledge on the biodiversity of Angola, based on sources in peer-reviewed journals, in books and where appropriate, unpublished official reports. The book identifies Angola as one of the most biologically diverse countries in Africa, but notes that its fauna, flora, habitats and the processes that drive the dynamics of its ecosystems are still very poorly researched and documented. This 'state of the science' synthesis is for the use of all students of Angola's biodiversity, and for those responsible for the planning, development and sustainable management of the country's living resources. The volume brings together the results of expeditions and research undertaken in Angola since the late eighteenth century, with emphasis on work conducted in the four decades since Angola's independence in 1975. The individual chapters have been written by leaders in their fields, and reviewed bypeers familiar with the region.